The Taiji and Eight Trigrams chemistry philosophy of chiral iridium(iii) complexes with triplex stereogenic centers. Issue 12 (26th February 2018) - Yan, Zhi-Ping; Luo, Xu-Feng; Liao, Kang; Lin, Zi-Xuan; Wu, Zheng-Guang; Zhou, Yong-Hui; Zheng, You-Xuan
Abstract : Eight Ir(iii ) isomers with triplex stereogenic centers are corresponding to the old Chinese philosophy Taiji and Eight Trigrams. The ECD and CPL spectra of four pair isomers show perfect mirror-images with a g lum factor around 0.003. Abstract : Four novel chiral iridium(iii ) complexes with triplex stereogenic centers were synthesized by introducing chiral carbon atoms into cyclometalated and ancillary ligands, and separated into eight isomers, which coincide with the old Chinese philosophy Eight Trigrams. The electron circular dichroism and circularly polarized luminescence spectra of four pairs of isomers show perfect mirror images with a dissymmetry factor ( g lum factor) of around 0.003.